The Relevance of The Firm Performance Status and Corporate Governance - Nurfala Safitri; Rika Lidyah; Titin Hartini; Maya Panorama; Chandra Zaki Maulana (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2022)
This study aims to determine the effect of managerial ownership and “Institutional Ownership“ on Firm Performance. This research uses eviews and excel for data processing. There are 7 companies that are sampled in this study. Based on the calculation results, the t-count is -1.305926 > t-table -2.042 with a significance number of 0.2009 > = 0.05, so Ho is accepted and Ha is rejected. This means that there is no influence of Managerial Ownership on Firm Performance. The magnitude of the influence of Managerial Ownership on Firm Performance = -0.881909 or 88.19% with a significance number of 0.2009> = 0.05. To reduce this deviant behavior, there is a need for supervision by outside parties. Share ownership by institutions can reduce deviant behavior by managers by conducting supervision. Based on the calculation results, the t-count is -2.889903 > t-table -2.042 with a significance number of 0.0069 < = 0.05, so Ho is rejected and Ha is accepted. This means that there is no an influence of “Institutional Ownership“ on Firm Performance. The results of this study are in line with agency theory.